2016
DOI: 10.21548/36-2-957
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity and Dynamics of Indigenous Yeast Communities in Grape Must from Vineyards Employing Different Agronomic Practices and their Influence on Wine Fermentation

Abstract: The current study evaluated the diversity of yeast species in Cabernet Sauvignon grape must derived from three neighbouring vineyards from a similar terroir but on which significantly different management practices are employed. The fermentation kinetics and yeast population dynamics were monitored from the beginning to the end of spontaneous fermentation. The grape musts were characterised by distinct yeast populations comprising oxidative, weakly fermentative and strongly fermentative yeasts. Different combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
1
19

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(83 citation statements)
references
References 33 publications
(46 reference statements)
8
54
1
19
Order By: Relevance
“…P. anomala was found throughout different vineyards over a period of three years in conventional and organic vineyards, representing approximately 20% and 25% of yeast species isolated from musts obtained from Grenache and Shiraz varieties [27]. In a similar study, W. anomalus was the second dominant yeast after Hanseniaspora uvarum in Cabernet Sauvignon grape must derived from integrated vineyards [28]. However, it was observed that the cell concentration of W. anomalus only increased marginally throughout fermentation, suggesting that its growth is severely hampered by the lack of oxygen [28].…”
Section: W Anomalus Is a Ubiquitous Yeast Generally Associated With mentioning
confidence: 73%
See 1 more Smart Citation
“…P. anomala was found throughout different vineyards over a period of three years in conventional and organic vineyards, representing approximately 20% and 25% of yeast species isolated from musts obtained from Grenache and Shiraz varieties [27]. In a similar study, W. anomalus was the second dominant yeast after Hanseniaspora uvarum in Cabernet Sauvignon grape must derived from integrated vineyards [28]. However, it was observed that the cell concentration of W. anomalus only increased marginally throughout fermentation, suggesting that its growth is severely hampered by the lack of oxygen [28].…”
Section: W Anomalus Is a Ubiquitous Yeast Generally Associated With mentioning
confidence: 73%
“…In a similar study, W. anomalus was the second dominant yeast after Hanseniaspora uvarum in Cabernet Sauvignon grape must derived from integrated vineyards [28]. However, it was observed that the cell concentration of W. anomalus only increased marginally throughout fermentation, suggesting that its growth is severely hampered by the lack of oxygen [28]. This yeast generally shows low growth rates and biomass yields under anaerobic conditions [15].…”
Section: W Anomalus Is a Ubiquitous Yeast Generally Associated With mentioning
confidence: 95%
“…Alcoholic fermentation of grape juice or "grape must" is commonly initiated by complex microbial consortia composed of oxidative, weakly fermentative and strongly fermentative species [1][2][3][4] . During the fermentation process, and dependent on the specific microbiota composition of each must, weakly fermentative yeast species such as Pichia terricola, Metschnikowia pulcherrima and Hanseniaspora uvarum are usually replaced by more strongly fermentative species such as Lachancea thermotolerans and Torulaspora delbrueckii, while Saccharomyces cerevisiae will generally complete the process when alcohol levels are high and oxygen is depleted [5][6][7][8][9][10] .…”
mentioning
confidence: 99%
“…By the end of fermentation, the microbial diversity is limited to selected microbial species [12,35]. As revealed by several studies, some species were found to decline rapidly at the initial or the middle stages of fermentation, such as Cryptococcus carnescens, Paraburkholderia terricola, Aureobasidium pullulans, and Metschnikowia pulcherrima, while others exist until the end of fermentation, including Saccharomyces cerevisiae, Torulaspora delbrueckii, Lachancea thermotolerans, and Streptomyces bacillaris [44][45][46][47].…”
Section: Identification Of the Microbial Communitiesmentioning
confidence: 99%